Solubilization and thermodynamic properties of simvastatin in various micellar solutions of different non-ionic surfactants: Computational modeling and solubilization capacity. - Faiyaz Shakeel; Sultan Alshehri; Mohamed A Ibrahim; Mohammad Altamimi; Nazrul Haq; Ehab M Elzayat; Gamal A Shazly (PLoS ONE)
The aim of this work was to solubilize simvastatin (SIM) using different micellar solutions of various non-ionic surfactants such as Tween-80 (T80), Tween-20 (T20), Myrj-52 (M52), Myrj-59 (M59), Brij-35 (B35) and Brij-58 (B58). The solubility of SIM in water (H2O) and different micellar concentrations of T80, T20, M52, M59, B35 and B58 was determined at temperatures T = 300.2 K to 320.2 K under atmospheric pressure p = 0.1 MPa using saturation shake flask method. The experimental solubility data of SIM was regressed using van't Hoff and Apelblat models. The solubility of SIM (mole fraction) was recorded highest in M59 (1.54 x 10-2) followed by M52 (6.56 x 10-3), B58 (5.52 x 10-3), B35 (3.97 x 10-3), T80 (1.68 x 10-3), T20 (1.16 x 10-3) [the concentration of surfactants was 20 mM in H2O in all cases] and H2O (1.94 x 10-6) at T = 320.2 K. The same results were also recorded at each temperature and each micellar concentration of T80, T20, M52, M59, B35 and B58. "Apparent thermodynamic analysis" showed endothermic and entropy-driven dissolution/solubilization of SIM in H2O and various micellar solutions of T80, T20, M52, M59, B35 and B58.